A reappraisal of the genus Megacaryon (Boraginaceae, Lithospermeae) based on molecular, morphological, and karyological evidence. Issue 6 (2nd November 2017) - Selvi, Federico; Cecchi, Lorenzo; Hilger, Hartmut H.; Coppi, Andrea
Abstract : The systematic position and phylogenetic relationships of Echium orientale, a rare endemic of the mountains of northern Turkey, were elucidated based on morphological, molecular, and karyological evidence. Using nuclear and plastid DNA sequences, we found that this species is not included in Echium, but is rather at least as divergent from it as other related lineages, namely the South African Lobostemon and Echiostachys . Pollen characters revealed a strong affinity with Onosma, especially in the non-reticulate ornamentation of the tectum. Fruit morphology is unique in the genera of the Echium 'alliance' (e.g. Echium, Pontechium, Lobostemon, and Echiostachys ), because of the large size and the smooth, glossy nutlet surface as in most species of Onosma . Karyological observations show that this species is diploid with 2n = 12, and differing from both Lobostemon or Echium, where nearly all species have higher numbers (usually 2n = 14 and 2n = 16, respectively). Combined with a 'megaherb' habit, the weak zygomorphism of the large flowers and a restricted range in the humid mountain forests of the Black Sea region, fruit, pollen and chromosome characters suggest an isolated position for E. orientale in the Echium alliance. We therefore propose its placement in the monotypic Megacaryon, a genus originally described by Boissier, but largely disregarded by later botanists. An original specimen is designated as generic lectotype.